THE SPIRIT OF ENTREPRENEURSHIP IN BUSINESS STUDENTS, NON-BUSINESS STUDENTS, AND SMALL AND MEDIUM ENTREPRENEUR - Niluh Made Dian Novita Handayani Narsa; I Made Narsa; Niluh Putu Dian Rosalina Handayani Narsa (Jurnal Manajemen dan Kewirausahaan, 2019)
There is debate as to whether entrepreneurs are born or can be created through education. Many business schools were established to produce entrepreneurs, but the fact is that many succesful entrepreneurs are not graduates of business schools. This study aims to examine empirically the entrepreneurial spirit of three different sample groups students who undertook a business course (accounting students), non-business students (engineering students), businessmen who are already involved in business activities (entrepreneurs). This study used a survey method. Data were analyzed using ANOVA. The total sample of this research were 254 respondents. The result showed that there was no empirical evidence regarding the entrepreneurial differences in the three groups. It was concluded that entrepreneurial skills are either there or not from birth. Business courses are not (or not yet) capable of triggering the entrepreneurial skills in a person